Synthesis and characterization of an f‑block terminal parent imido [U=NH] complex: a masked uranium(IV) nitride - King, David M.; McMaster, Jonathan; Tuna, Floriana; McInnes, Eric J.L.; Lewis, William; Blake, Alexander J.; Liddle, Stephen T. (American Chemical Society, 2014)
Deprotonation of [U(TrenTIPS)(NH2)] (1) [TrenTIPS = N(CH2CH2NSiPri3)3] with organoalkali metal reagents MR (M = Li, R = But; M = Na−Cs, R = CH2C6H5) afforded the imido-bridged dimers [{U-(TrenTIPS)(μ-N[H]M)}2] [M = L −Cs (2a−e)]. Treatmentof 2c (M = K) with 2 equiv of 15 crown-5 ether (15C5) afforded the uranium terminal parent imido complex [U(TrenTIPS)(NH)][K(15C5)2] (3c), which can also be viewed as a masked uranium(IV) nitride. The uranium−imido linkage was found to be essentially linear, and theoretical calculations suggested σ2π4 polarized U−N multiple bonding. Attempts to oxidize 3c to afford the neutral uranium terminal parent imido complex [U(TrenTIPS)(NH)] (4) resulted in spontaneous disproportionation to give 1 and the uranium−nitride complex [U(TrenTIPS)(N)] (5); this reaction is a new way to prepare the terminal uranium−nitride linkage and was calculated to be exothermic by −3.25 kcal mol−1.